Adult and continuing education in Norway - Bjerkaker, Sturla [Verfasser] (Bertelsmann, 2016)
"This publication gives an overview of central aspects of adult and continuing education in Norway. Sturla Bjerkaker presents a range of data and information regarding adult and continuing education institutions, financing, provision, participation, staff and international relationships. He describes adult and continuing education in Norway taking into consideration the political, geographical, and cultural context as well as the current economic situation. This book offers a brief and systematic introduction and guides the reader through the system of adult and continuing education in Norway." (Editor, BIBB-Doku)
Keywords: S 1.5 Weiterbildung; I 2.2 Europa; Erwachsenenbildung; Weiterbildung; Bildungspolitik; Norwegen